2010
DOI: 10.1007/s13197-010-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing parameters on textural characteristics and overall acceptability of millet enriched biscuits using response surface methodology

Abstract: Five blends of refined wheat flour (RWF) (63.2 -96.8, %RWF) and millet were used to manufacture biscuits baked for varying time (3.3-6.7 min) and temperature (166.6 -183.4°C). The manufactured biscuits were evaluated in terms of textural attributes (crispness, hardness and cutting strength) and overall acceptability (OAA). Results showed that increasing the amount of RWF in biscuits decreased (p < 0.01) hardness. Prolonging the baking time led to a decrease (p < 0.01) in hardness and cutting strength and a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 5 publications
3
23
0
1
Order By: Relevance
“…Replications of runs at the center points were used to estimate the experimental error and to allow for checking the adequacy of the second-order model. Model analysis, which included checking the validity of the model with the help of various relevant statistical aids, such as-F-value, coefficient of determination (R 2 ) and coefficient of variation (c.v.) revealed that all the models were statistically adequate (Chakraborty et al 2011). The result of the regression analysis and analysis of variance (ANOVA) for all the models is reported in Table 2.…”
Section: Discussionmentioning
confidence: 92%
“…Replications of runs at the center points were used to estimate the experimental error and to allow for checking the adequacy of the second-order model. Model analysis, which included checking the validity of the model with the help of various relevant statistical aids, such as-F-value, coefficient of determination (R 2 ) and coefficient of variation (c.v.) revealed that all the models were statistically adequate (Chakraborty et al 2011). The result of the regression analysis and analysis of variance (ANOVA) for all the models is reported in Table 2.…”
Section: Discussionmentioning
confidence: 92%
“…It is a faster and less expensive method for gathering research result than the classical method. RSM has successfully been applied for the development and optimization of the cereal products (Thakur and Saxena 2000;Singh et al 2004;Chakraborty et al 2011;Vijayakumar and Boopathy 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Wadikar et al (2010) developed the ginger based ready-to-eat appetizers using RSM. Chakraborty et al (2011) optimized the parameters on textural and overall acceptability of millet enriched biscuits using RSM.…”
Section: Introductionmentioning
confidence: 99%